Characterization of Hypoglycemic Constituents in Momordica charantia L. and their Hypoglycemic Effect - Guo, Shan-Bin; Tian, Yue; Jian, Ling-Yan (Asian Journal of Chemistry, 2015)
This study represents the active constituents in Momordica charantia L. and their hypoglycemic effect. Active constituents in Momordica charantia L. were extracted by ethanol percolation extraction and purified by macroporous resin method and preparative thin layer chromatography, post-administration blood glucose in mice was measured using mice model of STZ diabetes. Four compounds were isolated from Momordica charantia L., the determination of blood glucose, hepatic glycogen and fructosamine in mice indicated that blood glucose in mice was lowered after administration of Momordica charantia L. It is suggested that Momordica charantia L. has a hypoglycemic effect.